PENENTUAN NILAI SUN PROTECTION FACTORS (SPF) PADA EKSTRAK DAUN SURIAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Alyani Nur Shadrina; Erwin -; Chairul Saleh (Jurusan Kimia FMIPA UNMUL, 2025)
Excessive exposure to ultraviolet (UV) radiation can cause various negative effects on the skin, including erythema, hyperpigmentation, premature aging, and even skin cancer. The use of natural-based sunscreens is considered a safer and more environmentally friendly alternative to synthetic sunscreens. This study aimed to determine the Sun Protection Factor (SPF) of the crude extract and fractions of surian leaves (Toona sinensis (Juss.) M. Roem) using a UV-Vis spectrophotometer based on Mansur's equation. Extraction was carried out by maceration with 96% ethanol, followed by liquid-liquid partition using solvents with different polarities, namely n-hexane, ethyl acetate, and ethanol-water. Phytochemical screening showed the presence of bioactive compounds such as phenolics, flavonoids, quinones, tannins, and steroids, which are known to have photoprotective potential. The SPF test results revealed that the ethyl acetate fraction had the highest SPF value of 34.34 at a concentration of 250 ppm, classified as ultra-protection. The ethanol extract and ethanol-water fraction also showed high SPF values of 31.02 and 24.51, respectively, while the n-hexane fraction had the lowest SPF value. These findings indicate that surian leaves, particularly the ethyl acetate fraction, have promising potential as an active ingredient in natural sunscreen formulations.